A systematic review of implementation strategies to deliver guidelines on obstetric care practice in low‐ and middle‐income countries. Issue 1 (24th October 2016) - Imamura, Mari; Kanguru, Lovney; Penfold, Suzanne; Stokes, Tim; Camosso‐Stefinovic, Janette; Shaw, Beth; Hussein, Julia
Abstract: Background: Healthcare measures to prevent maternal deaths are well known. However, effective implementation of this knowledge to change practice remains a challenge. Objectives: To assess whether strategies to promote the use of guidelines can improve obstetric practices in low‐ and middle‐income countries (LMICs). Search strategy: Electronic databases were searched up to February 7, 2014, using relevant terms for implementation strategies (e.g. "audit, " "education, " "reminder"), and maternal mortality. Selection criteria: Randomized and non‐randomized studies of implementation strategies targeting healthcare professionals within the formal health services in LMICs were included. Data collection and analysis: Cochrane methodological guidance was followed. Because of heterogeneity in the interventions, a narrative synthesis was completed. Main results: Nine studies met the inclusion criteria. Moderate‐to‐low‐quality evidence was found to show improvement in the areas of doctor–patient communication (one study), analgesic provision (one study), the management of emergencies (two studies) and maternal and late neonatal mortality (one study each). Intervention effects were not consistent across studies. Conclusions: Implementation strategies targeting health professionals could lead to improvement in obstetric care in LMICs. Future research should explore what feature of an intervention is effective in one context and how this could be translated into another context. PROSPERO: CRD42014010310 Abstract : Moderate‐to‐low‐quality evidence suggests that interventions to implement guidelines could improve obstetric care in low‐ and middle‐income countries.